(untitled) (Journal of EAHIL, 2020)
Moving the Lausanne medical library to a new location was the opportunity to investigate how to best support the educational, training, clinical and research needs of both the Medical Faculty and the medical community across all disciplines. Our analysis is based on a tridimensional approach. First, we examine the role of the library as space provider, especially for the students and educational staff. Second, we reflect to what extent we could improve as an online resources provider and trim the print collection. Finally, we underline the importance to position the library as solution provider geared towards clinicians and researchers.